Reorganización contable por el sistema de cuenta múltiple en Ferrocentro Unimax de la ciudad de Loja, periodo enero – marzo de 2016 - Alulima Padilla, Ana del Carmen (2016)
Of degree work called "Accounting reorganization" by the system of Multiple account in Ferrocentro the city of Loja, in the period January - March 2016 UNIMAX was as one of the requirements prior to choose the title of engineer in accounting and auditing accountant public Auditor according to provisions in the rules of academic regime of the National University of Loja. In which arose the following general objective "Accounting reorganization by the system of Multiple account in Ferrocentro the city of Loja, in the period January - March 2016 UNIMAX" and the specific objectives, the plan of accounts with their respective manual according to the accounts used by the company, then prepares the initial inventory of goods be able to continue with the journal major general, balance checking and the respective statements by applying the accounting by the system features multiple process, with their respective auxiliary. With the results obtained from the work of qualification is set through the Organization of the accounting control allowing the owner know their financial economic reality of the company which helps decision-making and improve economic solvency in a set period of time.